Proposta para inserção do farmacêutico nos núcleos ampliados de saúde da família e atenção básica - NASF-AB - Félix, Carla Costa (2023)
The Núcleo Ampliado à Saúde da Família e Atenção Básica (NASF-AB) is involved in the daily life of Primary Care, integrating professionals, carrying out a multidisciplinary work in population caring. The NASF-AB matrix for the Family Health Strategy (ESF) materializes through the knowledge and practices exchange among professionals, as well as through the agreed articulation of interventions and sharing of ESF responsibilities and problems. The pharmaceutical professional can compose the team and act in clinical-assistance and technicalpedagogical activities, common to other NASF-AB professionals, in addition to carrying out their specific professional attributions. With this, the objective of this work is to develop a proposal for the insertion and maintenance of the pharmaceutical professional in the NASF-AB in a city in the interior of Rio Grande do Sul (RS). For this, through an integrative literature review, a search was carried out in relation to the importance of the pharmacist in the NASFAB, listing their attributions as a professional nucleus and highlighting the importance of their contributions in the territory and in the permanent education in health actions. With the insertion and maintenance of the NASF-AB in the municipality where the study was carried out, the continuity of pharmaceutical care emerged as a challenge in the sense of strengthening the existing structure. From this work, it was possible to verify the need to prepare pharmaceutical professionals and other professionals of the health team from graduation onwards for interdisciplinary work and for comprehensive and humanized care in the users health.